The Interspecific Abundance–Occupancy Relationship in Invertebrate Metacommunities Associated with Intertidal Mussel Patches - Ricardo A. Scrosati (Ecologies)
To explain the distribution and abundance of species, ecology searches for general models. A pattern often encountered in nature is the interspecific abundance–occupancy relationship (AOR), which describes how the mean local abundance of species relates to the proportion of local sites that each species occupies. Both are central variables in ecology and are often positively correlated, although exceptions have been found. As most AOR research has been conducted with terrestrial systems, recent studies are testing for its occurrence in marine systems. This contribution tests the AOR for invertebrate metacommunities associated with intertidal mussel patches. Using data from six coastal locations in Nova Scotia (Canada), this study shows that the negative binomial model properly describes the relationship between abundance and occupancy for these systems. The degree of wave exposure (wave-sheltered versus wave-exposed habitats) had some influence on the shape of the AOR. Overall, these findings extend the applicability of the AOR to intertidal invertebrate metacommunities. The raw data are included as part of this article to help future syntheses on the AOR, which will need data for a variety of terrestrial and aquatic environments.